ANALISIS KOMPETENSI PEDAGOGIK GURU MADRASAH IBTIDAIYAH AL-IRSYAD AL-ISLAMIYYAH HAURGEULIS INDRAMAYU - Nurlaeli Rohmah; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
Competence is an ability that must be possessed by teachers in carrying out their duties as educators. One of the competencies that must be possessed by teachers is the ability to manage learning, namely pedagogical competence. The purpose of this study was to determine pedagogical competencies possessed by Madrasah Ibtidaiyah Al-Irsyad Al-Islamiyyah teachers. This type of research is a qualitative research with descriptive methods. Data collection techniques are done through interviews, observation, and documentation. The subjects of the study were 6 teachers teaching Madrasah Ibtidaiyah Al-Irsyad Al-Islamiyyah. The results showed that the pedagogical competence of Madrasah Ibtidaiyah Al-Irsyad Al-Islamiyyah Haurgeulis teachers, based on PP Number 19 Article 28 Paragraph 3 (a), which amounted to 5 components of pedagogical competencies that must be possessed by teachers, namely there are two components that are in the good category, and the three component categories are sufficient. Competence of understanding of learners and evaluation of learning outcomes of teacher competence has been good. But the competence of learning planning, learning implementation, and student development to actualize the potential it has, the competency of teachers is in the sufficient category.